Immobilization of invertase on functionalized mesoporous silica and properties of the immobilized biocatalyst - Prabhune, Asmita Ashutosh; Sulabha, Karandikar; Archana, Pundle; Shilpa, Deshpande; Sanjeevani, Pardhy (Research Journal of Biotechnology, 2007)
Invertase, which catalyses the hydrolysis of sucrose, is one of the simplest commercial carbohydrases and is used for the production of invert syrup (mixture of glucose and fructose). Fructose is the sweetest natural sugar having beneficial medicinal effects and is emerging as an alternative sweetener to sucrose in the pharmaceutical industry. beta fructofuranosidase (E C 3.2.1.26) purified from Kluyveromyces marxianus NCYC 2675, a thermotolerant yeast, was immobilized on functionalized mesoporous silica SBA- 15. Attempts were made to immobilize invertase on functionalized silicalite and cross linked with glutaraldehyde so as to obtain a highly active and stable immobilized enzyme preparation suitable for commercial exploitation. Cross linked enzyme silica complex as well as enzyme silica complex showed very good temperature and pH stability. Extrudates of the mesoporous silica also showed similar results. Bound enzyme showed excellent stability to repeated use and retained 90% of its initial activity after ten cycles of reuse in batch mode.
Keywords: beta fructofuranosidase; extrudates; functionalized mesoporous silica; Invert syrup; invertase; SBA-15